PENGARUH APLIKASI UREA DAN KOMPOS TERHADAP SIFAT KIMIA TANAH SERTA PERTUMBUHAN JAGUNG (Zea mays L.) PADA TANAH TERDAMPAK ERUPSI GUNUNG KELUD - Sri Endah Agustin; Retno Suntari (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Mount Kelud that is one of the most active volcanoes in Indonesia, erupted on February 13, 2014. The eruption damaged agricultural crops in Trisulo Village Kediri. This study was conducted in greenhouse of the Faculty of Agriculture, Brawijaya University. Soil samples were taken from Trisulo Village, Posoklaten District, Kediri Regency. This study used a completely randomized design with five treatments and three replications. The treatments consisted of A1 (100% Urea), A2 (100% composted chicken manure), A3 (100% composted cow manure), A4 (50% urea + 50% composted chicken manure), and A5 (50% urea + 50% composted cow manure). Soil variables observed were soil pH, total N, C-organic, C/N ratio, and CEC. Plant parameters observed were plant height and number of leaves of maize. The results showed that application of chicken and cow manure composts with dosage of 100% (12,27 t ha-1 and 18,73 t ha-1) each significantly increased pH and CEC of soil affected by Mount Kelud Eruption compared to the use of 100% Urea , and could substitute the use of 50% Urea. As for the N-total of soil, only 100% (12,27 t ha-1) each application of chicken manure compost could substitute 50% urea. Application of chicken and cow manure composts with dosage of 100% (12,27 t ha-1 and 18,73 t ha-1) each significantly increased the number of leaves of maize plants, and could substitute the use of 100% (288 kg ha-1) urea, although the highest leaf number was obtained in combination dosage of 50% urea and 50% chicken manure compost.